2020
DOI: 10.3389/fmicb.2020.01940
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of Carbapenem- and Tigecycline-Resistant Proteus cibarius of Animal Origin

Abstract: The emergence of tet(X) and carbapenemase genes in Enterobacterales pose significant challenges to the treatment of infectious diseases. Convergence of these two categories of genes in an individual pathogen would deteriorate the antimicrobial resistance (AMR) crisis furthermore. Here, tigecycline-resistant Enterobacterales strains were isolated and detected with carbapenemase genes, characterized by antimicrobial susceptibility testing, PCR, conjugation assay, whole genome sequencing, and bioinformatics analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 32 publications
(63 reference statements)
3
15
0
Order By: Relevance
“…These data indicated that the increased expression of the tet(X6) gene will pose an extra burden on the bacteria growth of Enterobacteriaceae rather than the Proteus species. These results were consistent with previous findings that the overexpression of antibiotic resistance genes (ARGs) would inhibit the growth of certain bacteria and even lead to the death of bacteria [23,24]. We supposed that there are some regulation mechanisms or compensatory evolution that exist in P. mirabilis.…”
Section: P Mirabilis Hs1-t (Tet(x6)/pbad) 4supporting
confidence: 92%
“…These data indicated that the increased expression of the tet(X6) gene will pose an extra burden on the bacteria growth of Enterobacteriaceae rather than the Proteus species. These results were consistent with previous findings that the overexpression of antibiotic resistance genes (ARGs) would inhibit the growth of certain bacteria and even lead to the death of bacteria [23,24]. We supposed that there are some regulation mechanisms or compensatory evolution that exist in P. mirabilis.…”
Section: P Mirabilis Hs1-t (Tet(x6)/pbad) 4supporting
confidence: 92%
“…However, He et al discovered the plasmid-mediated mobile tigecycline resistance genes tet (X3) and tet (X4) in Enterobacteriaceae and Acinetobacter in 2019, which posed a severe threat to global public health ( 8 ). Of concern, previous studies have shown that tet (X4) has been found to coexist with mcr-1 or bla NDM-1 in the same strain ( 9 , 10 ). The strains resistant to multiple last-resort antibiotics regarded as new superbugs may disseminate globally.…”
Section: Introductionmentioning
confidence: 98%
“…So far, tet (X4) has been discovered in several bacteria species such as Escherichia coli , Aeromonas caviae , Acinetobacter sp., and Escherichia fergusonii ( 8 , 10 12 ). Meanwhile, the tet (X4) gene is widely distributed on plasmids of diverse replicon types ( 13 ).…”
Section: Introductionmentioning
confidence: 99%
“…The bla NDM gene is largely carried on plasmids with a variety of replicon types [ 3 ], which play a vital role in the wide dissemination of bla NDM . In Proteus spp., bla NDM was either integrated into an SXT/R391 integrative and conjugative element [ 9 , 10 ] on bacterial chromosomes, or carried on plasmids with unknown replicon types, such as the recently reported pPrY2001-like plasmids [ 11 , 12 ]. In fact, the genetic characters of bla NDM -harboring plasmids in Proteus remain largely uncharacterized.…”
Section: Introductionmentioning
confidence: 99%